Disfluency as a Desirable Difficulty—The Effects of Letter Deletion on Monitoring and Performance - Pieger, Elisabeth; Mengelkamp, Christoph; Bannert, Maria (Frontiers in Education, 2018)
Desirable difficulties initiate learning processes that foster performance. Such a desirable difficulty is generation, e.g., filling in deleted letters in a deleted letter text. Likewise, letter deletion is a manipulation of processing fluency: A deleted letter text is more difficult to process than an intact text. Disfluency theory also supposes that disfluency initiates analytic processes and thus, improves performance. However, performance is often not affected but, rather, monitoring is affected. The aim of this study is to propose a specification of the effects of disfluency as a desirable difficulty: We suppose that mentally filling in deleted letters activates analytic monitoring but not necessarily analytic cognitive processing and improved performance. Moreover, once activated, analytic monitoring should remain for succeeding fluent text. To test our assumptions, half of the students (n = 32) first learned with a disfluent (deleted letter) text and then with a fluent (intact) text. Results show no differences in monitoring between the disfluent and the fluent text. This supports our assumption that disfluency activates analytic monitoring that remains for succeeding fluent text. When the other half of the students (n = 33) first learned with a fluent and then with a disfluent text, differences in monitoring between the disfluent and the fluent text were found. Performance was significantly affected by fluency but in favour of the fluent texts, and hence, disfluency did not activate analytic cognitive processing. Thus, difficulties can foster analytic monitoring that remains for succeeding fluent text, but they do not necessarily improve performance. Further research is required to investigate how analytic monitoring can lead to improved cognitive processing and performance.